2022
DOI: 10.1155/2022/7145606
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of rCCK96-104PE38 Targeted Drug in the General Surgical Treatment of Colon Cancer

Abstract: To evaluate the clinical efficacy and safety of the rCCK96-104PE38 targeted drug in patients with colon cancer in general surgery, data of 80 patients with colon cancer who were admitted to the hospital from April 2019 to July 2021 were selected and randomly divided into the treatment group and the control group, with 40 cases in each group. Patients in the treatment group were treated with the rCCK96-104PE38 targeted drug, and those in the control group were treated with oxaliplatin. The treatment efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%